1999
DOI: 10.1021/cm981009r
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Nanospheres from Polyisoprene-block-poly(2-cinnamoylethyl methacrylate)-block-poly(tert-butyl acrylate)

Abstract: A polyisoprene-block-poly(2-cinnamoylethyl methacrylate)-block-poly(tert-butyl acrylate), PI-b-PCEMA-b-PtBA, sample with 3.7 × 10 2 units of isoprene, 4.2 × 10 2 units of CEMA, and 5.5 × 10 2 units of tBA was synthesized. The triblock formed spherical micelles with a PtBA corona, PCEMA shell, and PI core in THF/methanol with methanol volume fractions between 50% and 99%. After micellar structure "locking in" by UV cross-linking of PCEMA, the PI block of the triblock was degraded by ozonolysis to yield nanosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 26 publications
4
158
0
1
Order By: Relevance
“…Antonietti's group 79 used polybutadiene-block-poly(2-vinylpridine) (PB-b-P2VP) copolymers as templates for the synthesis of mesoporous silica. They found that, at a 50 wt % concentration of PB 210 -b-P2VP 99 in an aqueous solution, the 100 -150 nm pores were filled with multilamellar vesicles. Maskos and Harris 80 obtained double-shell vesicles and strings of vesicles from crosslinking poly(1,2-butadiene)-blockpoly(ethylene oxide) copolymers (PB 27 -b-PEO 28 ).…”
Section: Copolymer Systems Producing Vesiclesmentioning
confidence: 99%
“…Antonietti's group 79 used polybutadiene-block-poly(2-vinylpridine) (PB-b-P2VP) copolymers as templates for the synthesis of mesoporous silica. They found that, at a 50 wt % concentration of PB 210 -b-P2VP 99 in an aqueous solution, the 100 -150 nm pores were filled with multilamellar vesicles. Maskos and Harris 80 obtained double-shell vesicles and strings of vesicles from crosslinking poly(1,2-butadiene)-blockpoly(ethylene oxide) copolymers (PB 27 -b-PEO 28 ).…”
Section: Copolymer Systems Producing Vesiclesmentioning
confidence: 99%
“…It has been shown that the PAA shell can be cross-linked with a,x-diamino-poly(ethylene glycol) [50]. Similarly, a poly(isoprene)-b-poly(2-cinnamoylethyl methacrylate)-b-poly(tert-butyl acrylate) (PI-PCEMA-PTBA) triblock copolymer forms micelles with a PTBA corona, PCEMA shell and a PI core in THF-methanol mixtures [51]. In this case the micellar structure could be locked in by UV-cross-linking of the PCEMA within the micelles.…”
Section: 3mentioning
confidence: 99%
“…58 Similarly, a poly(isoprene)-block-poly(2-cinnamoylethyl methacrylate)-block-poly (tert-butyl acrylate) (PI-PCEMA-PTBA) triblock copolymer forms micelles with a PTBA corona, PCEMA shell and a PI core in THF and methanol mixtures. 59 In this case the micellar structure could be locked in by UV crosslinking of the PCEMA within the micelles. Subsequently the PI cores of both the crosslinked PI-PAA and the PI-PCEMA-PTBA micelles could be degraded by ozonolysis into small fragments that diffuse into the surrounding solution and nanospheres with a central cavity are left behind as produced.…”
Section: Figure 25 Procedures For the Preparation Of Nanocapsules Fromentioning
confidence: 99%
“…58 The potential of such systems for encapsulation of small molecules has been demonstrated by loading the crosslinked PCEMA-PTBA capsules with rhodamine B. 59 The incorporation of the dye into the central cavity of the particles could directly be visualized by TEM. The degradation of the shell crosslinked PI-PAA micelles leads to water-soluble crosslinked poly(acrylamide) hollow spheres, which possess considerably larger hydrodynamic diameter of their shells after removal of the core.…”
Section: Figure 25 Procedures For the Preparation Of Nanocapsules Fromentioning
confidence: 99%
See 1 more Smart Citation